Formal and Informal Communication Network Patterns in Continuing Information Fulfillment Among Urban Television Reporters - La Ode Muhammad Umran; Muhammad Arsyad; La Ode Herman H (International Journal of Integrative Sciences, 2023)
The pattern of formal and informal communication networks carried out by journalists, determines the information needs of strong and sustainable urban communities.  This study used a snowball technique.  Formal communication networks are carried out internally within the organization, editorial meetings are held once a day.  Informal communication networks obtain information from various circles, joining related organizations.  Fulfillment of information needs, starting from how journalists work in obtaining information, how to process information into news, the form of information obtained, and the extent of whistleblower awareness to obtain the information needed.  Communication established in the fulfillment of strong and sustainable information needs, by journalists is carried out in the public interest, not for a specific party.   And the contribution of this research is to provide guidance and ease in obtaining journalists' information, as well as in meeting the needs of strong and sustainable information in urban communities